Power is What Space Literally Creates - Hamidi, Nabil (My University, 2025)
Space gives rise to or produces power through three clear empirical principles: chronological priority, ontological independence, and necessary-condition analysis. First, scientific knowledge agrees that all manifestations of power emerged within space: systems of power developed inside a spatial environment, as every form of power became possible only because spatial conditions already existed. Second, power cannot exist without space, whereas space has clearly existed without power. This second principle is broadly recognized by scientists: space is a physical precondition, while power is a later, emergent phenomenon. Third, science recognizes that no form of human power—nor any form of power whatsoever—preceded space. Space existed roughly 14 billion years ago, long before the emergence of any power-bearing systems or processes. Therefore, because space predates all power, because power depends on distance for its existence, and because space does not depend on power, the conclusion follows directly: space originates power.